1979
DOI: 10.1111/j.1095-8649.1979.tb03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Some observations of the effects of body weight, temperature, meal size and quality on gastric emptying time in the turbot, Scophthalmus maximus (L.) using radiography

Abstract: The gastric emptying time (G.E.T.) in turbot was investigated using X-radiography and was found to decrease with bemperature. Small fish processed a given ration, expressed as per cent body weight, faster than large fish (G.E.T. was found to be proportional to (fisheight)^'^^^). Large meals in a given fish were processed at a faster rate than small meals. Gastric emptying rate (G.E.R.) was found to be proportional to (meal size g)o.ela at 8" C and (meal size g)0'7ss at 19" C. These exponents are in agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 32 publications
8
89
1
1
Order By: Relevance
“…The basis for this model is that digestion in fish is essentially a surface process. The results of Flowerdew & Grove (1979) and Grove et al (1985) on turbot Schopthalmus maximus L. also support the idea that digestion is a surface process. Enzymes attack the surface of the prey and work their way progressively deeper into the flesh.…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…The basis for this model is that digestion in fish is essentially a surface process. The results of Flowerdew & Grove (1979) and Grove et al (1985) on turbot Schopthalmus maximus L. also support the idea that digestion is a surface process. Enzymes attack the surface of the prey and work their way progressively deeper into the flesh.…”
Section: Methodssupporting
confidence: 73%
“…The corresponding estimate of dSo for coastal cod digesting two-spotted goby, 2.6 X 10-3 cm h-', was slightly higher than the 2.2 X 10-3 cm h-' which Salvanes et al (1995) found for Arctic cod digesting herring prey. Compared to previous empirical gastric evacuation curves, which have a separate d, for each temperature (Bagge 1977, Flowerdew & Grove 1979, Booth 1990), the approximation made in our analysis represents a simplification and thus a n improvement.…”
Section: Temperaturementioning
confidence: 97%
“…Experiments with trout, marine flatfish, and other fishes fed artificial diets have shown increased evacuation rates when fed on diets low in energy (Rozin & Mayer 1961, Grove et al 1978, Flowerdew & Grove 1979, Jobling 1980, 1981a, Jobling & Wandsvik 1983). Since appetite is related to stomach or foregut fullness, feeding rate is strongly influenced by gastric or foregut emptylng rate (Grove et al 1978, Fange & Grove 1979, Grove & Crawford 1980, Holmgren et al 1983, Knights 1985, Horn 1989.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation between rate of energy intake and total transit time may be a result of the correlation between weight of food ingested and rate of energy intake. In several studies with teleosts, lowered energy density of food resulted in an increased rate of gastric evacuation (Grove et al 1978, Flowerdew & Grove 1979). An increased rate of gastric evacuation allows a fish to process low energy food more rapidly, which means that more food may be consumed and energy demands of the fish can be met in this way (Lee & Putnam 1973, Page & Andrews 1973.…”
Section: Discussionmentioning
confidence: 99%